HUMAN RESOURCE MANAGEMENT OUTSOURCING MODELS FOR INDUSTRIAL ESTABLISHMENTS IN THE FUTURE - เก้าประเสริฐ, นาถญาดา; วิรุณราช, บรรพต (RMUTT Global Business and Economics Review, 2016)
This study was conducted with the objective of examining human resource management outsourcing models for industrial establishments in the future. The study was based on a qualitative research design. Data was collected from the main group of 20 participants by interview method. Data was analyzed by using content analysis in order to organize human resource activities in order to obtain data in concurrence with the research objectives. According to the research findings, human resource management outsourcing models for industrial establishments in the future involve the following 25 activities: (1) design and benefit management, (2) research of human resource (3) training and development (4) payroll systems, (5) employment organizations (6) preemployment testing (7) recruitment and selection (8) compensation and salary surveys (9) employment after termination of employment (10) technology access (11) employee satisfaction (12) competitive benchmarking, (13) organization development and design (14) human resource information systems and human resource information technology (HRIS/ HRIT) (15) customer satisfaction (16) human resource strategic planning (17) cost reduction (18) happiness workplace (19) employee aid programs (20) healthcare systems and safety (21) expatriate, (22) organization satisfaction (23) lack of resources reductions (24) total human resource outsourcing (25) focus on core competencies. These 25 human resource management activities by external management agencies can result in organization savings, fairness for all stakeholders, ability to access technological innovations and ability to access specific field expert. With this advantages, the organizations among industrial establishments in the future can then have more effective human resource management.